Ordered Convex Metric Spaces. (25th October 2021) - Beg, Ismat
Abstract : The aim of this article is to introduce a new notion of ordered convex metric spaces and study some basic properties of these spaces. Several characterizations of these spaces are proven that allow making geometric interpretations of the new concepts.